A comparison of methods for the evaluation of the physiological quality of soybean seeds with emphasis to the use of the electrical conductivity test. - Filho, Júlio Marcos; Silva, Walter Rodrigues da; Novembre, Ana D. Coelho; Chamma, Helena M. C. Pescarin (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was set at the Agriculture Dept., ESALQ/USP, Piracicaba, Brasil, between October/ 1987 and April 1988 with the purpose of comparing the efficiency of diferent tests in evaluating the physiological quality of seeds from three soybean (Glycine max (L.) Merrill) cultivars. The comparisons included the germination, tetrazolium, cold, accelerated aging, electrical conductivity and field emergence tests. Different imbibition periods for the electrical conductivity test were also compared. It was concluded that the physiological quality of soybean seeds is best estimated when based upon results from several different tests. Among them, the shorter imbibition periods (4 and 8 hours) for the bulk conductivity test can be used for the detection of wide vigor differences, while a 16 or 20 hours imbibition period can be used for identifying smaller differences among soybean seed lots.